Komunikasi Interpersonal Barista Dalam Menciptakan Kepuasan Pelanggan: (Studi Kasus Pada Barista Emercel Coffee Studio Surakarta) - Milanuari, Winda; Sekarwangi, Maya; Astuti Itasari, Andri (Solidaritas, 2024)
Data from the Ministry and Data Center show an increase in domestic coffee consumption over the past five years, including in Surakarta City. Emercel Coffee Studio, which has a co-working space theme, has become the main choice for young people and WFA (Work From Anywhere) workers. After implementing the Training of Service program in 2022, Emercel Coffee Studio experienced a 15% increase in the number of customers, and reviews showed a significant increase in satisfaction with the service, indicating a correlation between the quality of interpersonal communication practiced by the baristas and customer satisfaction.This study aims to describe the interpersonal communication between baristas and customers at Emercel Coffee Studio that contributes to customer satisfaction. This research uses the theory of interpersonal communication effectiveness developed by DeVito. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation.The results of the study show that in the component of equality, there is an age-based imbalance, where baristas find it easier to communicate with younger customers compared to older ones. However, in the components of openness, empathy, support, and positive attitude, interpersonal communication has been going well and meets customer expectations. Baristas demonstrate openness by sharing detailed information about the menu and responding honestly to customer feedback; empathy by understanding and meeting customer needs; support by providing personal attention; and a positive attitude through friendliness and warm greetings. Thus, effective interpersonal communication by baristas is key to creating a positive experience and increasing customer satisfaction at Emercel Coffee Studio. Keywords: Interpersonal communication, barista, customer satisfaction